Fédération de botanistes, synthèse de contributions citoyennes et transfert de la connaissance naturaliste - Delphine Montagne (Netcom)
Tela Botanica is an association dedicated to botany. It relies on the Internet and new technologies to develop a French naturalist network. This note recalls its construction, technical and organizational features. Which have enabled the success and development of multi-thematic projects in the service of naturalist knowledge.